A New Development in Topological Analysis of Propane Para-Line Graphs with Application in Chemical Composition - Ahmad, Mukhtar; Yusof, Yuhani Binti; Qayyum, Ather; Rathour, Laxmi; Singh, Vinay; Mishra, Lakshmi Narayan (Discontinuity, Nonlinearity, and Complexity, 2026)
123 Topological indices are powerful tools in various fields of science and engineering. It also assist in assessing the environmental impact, biodegradability, and toxicity of chemical substances, supporting the creation of safer and more sustainable chemicals. It can be defined as a mapping from the molecular structure of a substance to a real number. Its purpose is to characterize the physicochemical properties of specific substances while maintaining its invariance under graph transformations. Molecular descriptors play a crucial role in mathematical chemistry, particularly in investigations involving quantitative structure-property relationships and quantitative structure-activity relationships. In the context of this study, we investigated the chemical composition of pentacene, focusing on various indices, including the general randić connectivity index, the first and second multiple zagreb indices, the first general zagreb index, the atomic bond connectivity index, the hyper-zagreb index, and the geometric-arithmetic index for propane paraline graphs of linear-pentacene, multi-pentacene and linear [n]-pentacene.